2018
DOI: 10.1007/s10900-018-0558-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Differences in CDC-Funded HIV Testing by Urbanicity, United States, 2016

Abstract: HIV prevention efforts have contributed to a decline in annual HIV infections in the United States. However, progress has been uneven and certain groups and geographic areas continue to be disproportionately affected. Subsequent to implementation of CDC's high-impact HIV prevention approach to reducing new infections, we analyzed national-level CDC-funded HIV test data from 2016 to describe the population being reached in three urbanicity settings (metropolitan: ≥ 1,000,000 population; urban: 50,000-999,999; r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Estudo realizado na Catalunha, Espanha, identificou que as maiores taxas de novos diagnósticos de HIV ocorreram em regiões localizadas em áreas urbanas, especialmente na cidade de Barcelona (28) . Outra pesquisa realizada nos Estados Unidos revelou diferenças estatisticamente significativas na distribuição de novos diagnósticos por características demográficas e ambiente urbano, com taxas de positividade para o HIV mais altas nas áreas urbanas (29) . Tais resultados corroboram com os achados desta pesquisa.…”
Section: Discussionunclassified
“…Estudo realizado na Catalunha, Espanha, identificou que as maiores taxas de novos diagnósticos de HIV ocorreram em regiões localizadas em áreas urbanas, especialmente na cidade de Barcelona (28) . Outra pesquisa realizada nos Estados Unidos revelou diferenças estatisticamente significativas na distribuição de novos diagnósticos por características demográficas e ambiente urbano, com taxas de positividade para o HIV mais altas nas áreas urbanas (29) . Tais resultados corroboram com os achados desta pesquisa.…”
Section: Discussionunclassified
“…A study conducted in Catalonia, Spain, identified that the highest rates of new HIV diagnoses occurred in regions located in urban areas, especially in the city of Barcelona ( 28 ) . Another study conducted in the United States revealed statistically significant differences in the distribution of new diagnoses by demographic characteristics and urban environment, with higher HIV positivity rates in urban areas ( 29 ) . These results corroborate the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The highest rates of new HIV diagnoses were in ABSs located in urban areas, especially the city of Barcelona. While differences between urban and rural areas have been reported [2], the fact that people living with HIV in rural areas are more likely to be diagnosed later than their urban counterparts [26,27] should be taken into account. Rural residents at risk for or living with HIV experience barriers that include greater local stigma about HIV infection, a socially conservative climate, and scarcity of funding for widespread testing and treatment programs [3].…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with the incidence of HIV infection have proven to be diverse and distributed both worldwide and within countries and transmission groups. Previous studies have revealed statistically significant differences in the distribution of new diagnoses by demographic characteristics and urban setting, with HIV positivity rates being higher in urban areas [2]. On the other hand, rural residents at risk for or living with HIV infection face unique challenges [2,3], namely, they are less likely to have been tested for HIV or have been tested in the past year than urban residents [4].…”
Section: Introductionmentioning
confidence: 99%